Experimental and Numerical Modeling of Versa Trap Type W - Ismail, Mohamed; Nikraz, Hamid; Khan, Azam (The CIGR EJournal, 2009)
This paper presents the results of experimentations carried out into the solids separation performance of a vortex combination. It also analyses the processes involved in this separation technique. VersaTrap type W (VTW) designed by Rocla for industrial wastewater treatment has been used in this project. The vortex is generated in a cylindrical chamber above the level of a cylindrical screen. Experimental and numerical analysis were performed on the scale model to establish the hydraulic characteristics and pollutant removal efficiencies (PRE). The VT type W with 0 and 50% blocked screen (for single and double baskets) was tested at Curtin University of Technology to replicate typical in situ conditions. The results were scaled up to provide data on the full range of full size units. Comparing Computational Fluid Dynamic (CFD) simulation and experimental results suggest that CFD software is an effective tool to assess the findings of the hydraulic treatment system. Data analysis has demonstrated that the headloss increases in proportion to flow rates. The removal efficiencies are inversely proportional to flow rates. The study outcomes have capabilities to optimize any other types of wastewater treatment systems.